Policy on Access, Quality and Competitiveness Islamic Education - Ahmad Zarkasyi (STAI Miftahul Ula Nganjuk, 2018)
1945 Constitution explicitly mandates that every citizen has the right to education because education is the main instrument to build a culture and civilization both the Islamic nation and Nor. Even Indonesian government has committed internationally to achieve the target of increasing the quality of education for all by 2015, there are still many issues concerning education in addition to the issue of access to education. Included in these issues is a matter of fairness and quality of education. To address these issues, the recommendations need to be provided based on evidence gathered from painstaking research in order to be relied upon by the government, to be used as a basis of an access, power quality competitiveness of education in the era of competition. Effective policy formulation process must pay attention to harmony between the agenda of policy proposals and strategies (grand design) government. The government also is not the sole actor in increasing accessibility of education. Communities also have an important role in improving the quality of life of their own.